Desain Dan Analisa Sistem Proteksi Petir Pada Rumah Sakit Universitas Riau - Maradongan, Maradongan; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
A lightning protection system is indispensable for the building that has a very vital function, such as Hospital. To protect the building from direct strike and indirect strike use of air terminationsystem and arrester. Among them are air termination system, Protection Angle Method, Method Jala, and Rolling Sphere Method. Building Riau University Hospital is a health care center built by size (p x l x t) 61m x 31m x 27m. To design a lightning protection system at the University Hospital of Riau note identifying the needs of a lightning protection system based PUIPP, the determination of the distance from the strike, election finial, determination conductor resistance values down andgrounding buildings. From the calculation of hazard assessment, the area of lightning strikes reach 37406.98 m2, the possibility of being struck by lightning strikes each year at 0.8915 with a lightning protection system efficiency by 0.883. Based on the results of the design and analysis of building structures Riau University Hospital using the ball rolling seen that the existing protection system can not protect the entire building well. From these results it appears that the building Riau UniversityHospital requires 8 finial placed on any area affected by stroke each finial 1 meter high and the ground is good enough prisoners of 3.5 ohms.Keywords : lightning protection system, rolling sphere method, distance strike